Pathophysiology, classification and available guidelines of acute pancreatitis - İnce, Ali Tüzün and Baysal, Birol (Turkish Journal of Gastroenterology, 2014)
Abstract Acute pancreatitis (AP) constitutes the majority of cases requiring hospital admission in gastroenterology. We are yet to know many things about its pathophysiology which is a certain drawback for the progress in its treatment.Prediction of severity is necessary for the plan of the management. The existing scoring systems are yet to be satisfactory. However our progress in the field was significant in the recent decade and a leap forward is expected in this cumbersome-to-manage condition which has many unmet needs. In this review, we are going to summarize the hitherto data in pathogenesis and would weigh the usefulnes and weaknes of each of existing scoring systems in the management of AP.